Impact of Primary Hypothyroidism on Rheumatoid Arthritis Patients - Abduwahab Muhammed, Marwa; Kader Media , Shwan (Diyala Journal of Medicine, 2022)
Background: Rheumatoid arthritis is a systemic inflammatory disease with unknown etiology. There has been considerable debate about the relation between thyroid gland and rheumatic diseases. Objective: To assessed the prevalence of primary hypothyroidism in patients with rheumatoid arthritis, as well as the association between hypothyroidism and the severity of rheumatoid arthritis. Patients and Methods: This study is a cross-sectional observational study involving 65 participants 18 years of age and older who were diagnosed with RA. Patients had thyroid function tests and patient disease activity was determined using the DAS28 Modified Disease Activity Score .the data were analyzed using the chi-square significance test with a P-value of ≤0.05. The data will be collected during the direct patient interview and the information from the questionnaire once verbal approval has been received from the study participant. Results: Hypothyroidism (thyroid stimulating hormone) level >4.20 µIU/L ) was observed in 26 (40%) parameters of disease activity such as DAS-28, counts tender joints significantly associated with hypothyroid patients RA. Conclusion: Hypothyroidism was significantly associated with disease severity of RA, disease duration, BMI (Body Mass Index), and ACPA (Anti Citrullinated Protein Antibody). Identification of thyroid function tests in patients with RA is important.